Uji Aktivitas Antimikroba Beberapa Ekstrak Bumbu Dapur terhadap Pertumbuhan Jamur Curvularia lunata (Wakk.) Boed. dan Aspergillus flavus LINK. - SITEPU, IRMA SELVYANA Br.; SUADA, I KETUT; SUSRAMA, I GEDE KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol. 1, No. 2, Oktober 2012, 2012)
ABSTRACT The Antimicrobial Activity Test of Some Kitchen Seasoning Extracts on Growth of Fungus Curvularia lunata (Wakk.) Boed. and Aspergillus flavus LINK. This research was aimed to determine the ability of herbs extract in inhibiting the growth of fungus C. lunata and A. flavus and to determine the minimum inhibition concentration of each extracts as well. The results showed that the extracts could inhibit the growth of the two fungus. The most effective extract was turmeric against C. lunata and galangal extract against A. flavus with each inhibition was 38,6% and 26,6% respectively. The minimum inhibition concentration of all extracts were 0,5% on both C. lunata and A. flavus . Keyword : Antimicrobial, Kitchen seasoning, Curvularia lunata, Aspergillus flavus
Keywords: Antimicrobial; Kitchen seasoning; Curvularia lunata; Aspergillus flavus